Microanalytical Study of Discontinuous Precipitaton in Aluminium-Zinc Alloys - Solorzano-Naranjo, Guillermo Ivan (My University, 1983)
This thesis treats the discontinuous mode of precipitation in Al-22 and 28 at .8 Zn. High resolution STEM x-ray microanalysis has been used to measure the composition profiles in individual depleted lamella formed under isothermal conditions. These data, combined with local values of cell velocity and interlamellar spacing, have been used to evaluatethe kinetic and thermodynamic quantities of main concern. It is shown that the reaction is grain boundary-diffusion controlled and depending of individual grain boundary characteristics. The driving force for grain boundary migration and possible free-energy sinks are discussed. The results are compared with predictions of existing theories.
The problem of the optimal interlamellar spacing is addressed, mainly from the experimental point of view. Experimental data for Al-Zn and Mg-Al alloys are analyzed and related to the discussion.
The problem of the optimal interlamellar spacing is addressed, mainly from the experimental point of view. Experimental data for Al-Zn and Mg-Al alloys are analyzed and related to the discussion.
It is demonstrated that initiation involves diffusion induced grain boundary displacements, and that during the growth process a significant amount of elastic energy is stored in the product phases. The dissolution of the reheated lamellar structure is volume diffusion-controlled.
Keywords: Materials Science and Engineering; Metallurgy; Materials Science and Engineering